Lifitegrast in Treatment of Dry Eye Disease—A Practical, Narrative Expert Review - Erlend C. S. Landsend; Mads Istre; Tor P. Utheim (Journal of Ophthalmology)
Conclusions: Based on the current literature, we conclude that lifitegrast could improve various parameters of DED. Still, larger controlled trials are required to establish additional benefits of this medication beyond those of other DED treatments.